Real Time Monitoring System on Solar Panel Orientation Control Using Visual Basic - Hamdani Hamdani; Ali Basrah Pulungan; Dwiprima Elvanny Myori; Fauzan Elmubdi; Teuku Hasannuddin (Journal of Applied Engineering and Technological Science (JAETS), 2021)
Problems that often occur in the use of solar panels are the efficiency of solar panels and monitoring of solar panel generating systems. Monitoring of the output parameters of solar panels is very necessary to assess the performance and efficiency of a solar panel in real environmental conditions. Internet of Things (IoT) can make devices communicate with each other such as sending and receiving data. A monitoring system based on a wireless sensor network was created to make it easier to get direct and real time information on the output parameter data of the solar panels. The research objective is to create a monitoring system on a solar panel using Visual Basic and Blynk applications. This system is designed to determine the output parameters of the solar panel in the form of current, voltage, light intensity, and position which are processed directly and displayed in tables and graphs in Real Time conditions. The use of logger data in this monitoring system is very important. From the results of tests carried out on this monitoring system, the system is able to record and read the output parameters regarding the resulting current and voltage data as well as light intensity and the position of the solar panels. Information about measurement data from each sensor will be stored in the database and can be obtained directly through an excel spreadsheet.